Molecular and pathological basis of HPV‐negative cervical adenocarcinoma seen in a global study. Issue 9 (6th July 2020) - Jenkins, David; Molijn, Anco; Kazem, Siamaque; Pirog, Edyta C; Alemany, Laia; de Sanjosé, Silvia; Dinjens, Winand; Quint, Wim
Abstract: International surveys find HPV‐negativity in up to 30% of cervical adenocarcinomas. We investigated the pathological diagnosis by expert consensus with immunohistochemistry and the presence of somatic mutations in recognised tumour genes in HPV‐positive and negative cervical adenocarcinomas (CADC). A sample was selected of 45 paraffin‐embedded cervical blocks diagnosed locally as usual cervical adenocarcinoma from a global study. These represented different diagnoses made at previous diagnostic review and HPV status. All were suitable for analysis for somatic tumour associated gene mutations. Three pathologists examined H/E slides and immunohistochemistry for p16, progesterone receptor and p53 and classified the cases. L1 genes from high‐risk HPVs and low‐risk HPVs were analysed by SPF10 PCR‐DEIA‐LiPA25 version 1 in whole tissue sections and microdissected tumour and retested by PCR for E6/E7 genes of hrHPVs if negative. Cases were analysed for microsatellite instability and next‐generation sequencing mutation analysis. From the 45 cases, 20 cases of usual CADC were confirmed of which 17 (85%) were HPV‐positive in tumour cells. The other 25 cases were reclassified as endometrial, serous, clear‐cell and gastric‐type adenocarcinomas and all were HPV‐negative in tumour cells. Careful retesting for HPV DNA and IHC leads to more accurate identification of HPV‐positive usual cervical adenocarcinomas. Endometrioid endometrial adenocarcinomas, other uterine adenocarcinoma with multiple somatic mutations were important in misclassification of HPV‐negative cases locally managed as cervical adenocarcinoma, as was gastric‐type adenocarcinoma with germline STK11 mutation in East Asia. Few consensuses confirmed HPV‐negative usual cervical adenocarcinomas showed somatic tumorigenic mutations also seen in some HPV‐positive usual CADC. Abstract : What's new? As many as 30 percent of cervical adenocarcinomas initially test negative for human papillomavirus (HPV), which is necessary but not sufficient for the development of cervical cancer. Here, the authors carried out an extensive survey of different categories of adenocarcinoma initially diagnosed and managed as cervical adenocarcinoma. Analyses show that misdiagnosis of endometrioid endometrial cancer and serous or clear cell cancers as cervical adenocarcinoma are not infrequent and that HPV‐negative cervical adenocarcinoma is a real, though infrequent diagnosis. The findings highlight issues of misdiagnosis and the role of somatic or germ‐line mutations in tumor genes in cervical adenocarcinoma.